Epinephrine Production in Th17 Cells and Experimental Autoimmune Encephalitis - Yang, Pinguang; Tian, Hong; Zou, Yong-Rui; Chambon, Pierre; Ichinose, Hiroshi; Honig, Gerard; Diamond, Betty; Kim, Sun Jung (Frontiers in Immunology, 2021)
Epinephrine is a hormone secreted primarily by medullary cells of the adrenal glands which regulates permeability of blood–brain barrier (BBB). Recent studies showed signaling by epinephrine/epinephrine receptor in T cells is involved in autoimmune diseases. Nevertheless, the production of epinephrine by T cells and its pathogenic function in T cells are not well investigated. Our results show that phenylethanol N-methyltransferase (PNMT), a rate-limiting enzyme of epinephrine synthesis, is specifically expressed in vitro in differentiated TH17 cells and in tissue-resident TH17 cells. Indeed, expression levels of enzymes involved in epinephrine production are higher in TH17 cells from animals after EAE induction. The induction of PNMT was not observed in other effector T cell subsets or regulatory T cells. Epinephrine producing TH17 cells exhibit co-expression of GM-CSF, suggesting they are pathogenic TH17 cells. To delineate the function of epinephrine-production in TH17 cells, we generated a TH17-specific knockout of tyrosine hydroxylase (Th) by breeding a Th-flox and a ROR-gt-CRE mouse (Th-CKO). Th-CKO mice are developmentally normal with an equivalent T lymphocyte number in peripheral lymphoid organs. Th-CKO mice also show an equivalent number of TH17 cells in vivo and following in vitro differentiation. To test whether epinephrine-producing TH17 cells are key for breaching the BBB, migration of T cells through mouse brain endothelial cells was investigated in vitro. Both epi+ wild-type and epi- TH17 cells migrate through an endothelial cell barrier. Mice were immunized with MOG peptide to induce experimental autoimmune encephalitis (EAE) and disease progression was monitored. Although there is a reduced infiltration of CD4+ T cells in Th-CKO mice, no difference in clinical score was observed between Th-CKO and wild-type control mice. Increased neutrophils were observed in the central nervous system of Th-CKO mice, suggesting an alternative pathway to EAE progression in the absence of TH17 derived epinephrine.